Assessing the Salt Tolerance of Sulla carnosa Genotypes by Agronomic Indicators. (1st January 2014) - Gandour, Mhemmed; Neji, Mohamed; Hessini, Kamel; Smida, Malek; Abdelly, Chedly; Taamalli, Wael
Abstract : The progressive salinization of arable lands at a rate of 3 ha min –1 worldwide is a major concern for agricultural crop production. The future of crop improvement to resist or tolerate environmental stresses requires selecting halophytes that will produce high yield and profit. A halophyte, Sulla carnosa ( Hedysarum carnosum Desf.), collected from southern and central Tunisia is considered a salt‐resistance species. A group of five populations represented by 150 genotypes (30 genotypes per population) were tested under greenhouse conditions with salt treatments 0 mM (control) and 300 mM (stressed). Fifteen agronomic traits related to vegetative and reproductive growth were evaluated for their responses to salinity stress. Analysis of the population effect and genotypes within population's effect shows that both population and genotype factors have a significant effect for almost all measured traits. The highest diversity in traits was found within progeny originating from Douiret and Kairouan populations (mean and CV across the 15 traits 48.4 and 46.5%, respectively). Level of phenotypic differentiation (Q_ST) varied according to measured traits; it ranged from 0.108 for flowering time to 0.63 for mean crown width with an average of 0.29. Means comparison and principal component analysis showed that six genotypes from different origins were ranked as salt tolerant and three others as salt sensitive. These findings indicate the potential for selecting plants or traits with improved salt tolerance within that species. The method used allows detection plants or traits with enhanced salinity tolerance after 2 mo of growth for the ability to grow at salt concentrations that prevent the growth of other plants.